Evaluation of endometrial polymerase chain reaction in diagnosis of female genital tuberculosis - Dua, Manvi; Pandey, Kiran; Arya, Sangeeta; Verma, Anil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Genital tuberculosis also known as tuberculous pelvic inflammatory disease can affect any age group, most common being reproductive women of 20-40 years. Clinical diagnosis of genital tuberculosis is a big challenge as the disease is either asymptomatic or has varied presentations. Conventional methods for diagnosis including AFB smear, endometrial histopathology and culture have limitations of low detection rate because of paucibacillary nature of disease. Laparoscopy generally detects macroscopic changes such as peritubal adhesions, tubercles and tubo-ovarian mass but it fails to diagnose disease at early stage. The objective of this study was to evaluate efficacy of TB DNA PCR in diagnosis of genital tuberculosis. Methods: A total of 127 patients (between 2013-2016) who presented in gynecologic OPD with symptoms suggestive of tuberculosis were included in the study. All patients were subjected to endometrial histopathology and TB DNA PCR of endometrial tissue and peritoneal fluid. Since there is no gold standard test available for diagnosis of genital tuberculosis, a diagnostic criteria was adopted in the study based on laparoscopic findings, clinical history and other investigations. Patients were divided in two groups. Group A included patients positive of tuberculosis based on diagnostic criteria. Group B included patients negative for tuberculosis based on diagnostic criteria. Results: In our study sensitivity of endometrial PCR, peritoneal PCR and endometrial histopathology were 73.8%,17.8% and 10.7% respectively. Endometrial histopathology and peritoneal fluid PCR was found to be highly specific (100%) while endometrial PCR was found to be 93% specific. Endometrial PCR although has highest sensitivity and specificity amongst the groups evaluated but high false negative rate was its major limitation. Conclusions: No single test fulfills all criteria to emerge as sole diagnostic test, hence a high degree of suspicion with a detailed history and investigating with a variety of tests is all that is required to diagnose geniatal tuberculosis.